PENINGKATAN LITERASI DIGITAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENDUKUNG IMPLEMENTASI KURIKULUM MERDEKA DI SMA ISLAM AL-ULUM TERPADU MEDAN - Sulastri A; Danny Abrianto (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
This study aims to investigate the enhancement of digital literacy in Islamic Religious Education (PAI) to support the implementation of the Merdeka Curriculum at Al-Ulum Integrated Islamic High School in Medan. (a) Digital literacy has become an essential skill in the era of the Industrial Revolution 4.0, where the ability to use, access, and evaluate information from digital sources is crucial for students' success. In the context of PAI, digital literacy not only aids students in better understanding religious values but also protects them from inaccurate information. The Merdeka Curriculum, recently introduced in Indonesia, encourages the integration of technology in education, providing flexibility for teachers and students to utilize digital tools to improve the quality of learning. (b) This study employs a qualitative research approach, involving interviews and observations conducted at Al-Ulum Integrated Islamic High School in Medan from September 30 to October 30, 2024. (c) The research findings indicate that the enhancement of digital literacy at the school positively impacts the PAI learning process. Digital technology facilitates access to more varied learning resources, resulting in a more interactive discussion and evaluation of religious materials. Achievements include the use of digital platforms such as Google Classroom, Al-Quran IPTEK, and digital libraries, which support students in accessing and critically understanding information. However, challenges persist, such as the need for teacher training and limited technological infrastructure at the school. (d) The study concludes that digital literacy has significant potential to enhance the effectiveness of PAI learning and support the development of students' character in alignment with Islamic values. Implementing suitable strategies, such as teacher training and technology-based program development, can help schools increase learning effectiveness and prepare students to face challenges in the digital era.